1983
DOI: 10.1007/bf03189585
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of disopyramide in patients with chronic renal failure

Abstract: The pharmacokinetics study of a single oral dose of 200 mg of disopyramide was performed in 22 normal control subjects and 33 patients with chronic renal failure (CRF). The latter were subdivided into 3 groups of 11 patients each as a function of the gravity of renal insufficiency. With the exception of maximum concentration (C max), which was only slightly modified, and of the apparent distribution volume which remained unchanged, all the other pharmacokinetic blood parameters (t max, concentration at 24th ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…In our / present study, mean CL/F and t1/2 of disopyramide / varied from 5263 mL/h and 9.95 hours in mild renal / function impairment to 3428 mL/h and 14.47 h in severe renal function impairment, respectively, and in / healthy 12 Japanese subjects mean CL/F and t1/2 / were reported to be 6173 mL/h and 6.05 h, respectively 12) . These results were in line with the study reported by Francois et al 2) . Since disopyramide Cmax was not affected, renal function impairment would affect disopyramide elimination from the body but not its absorption.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our / present study, mean CL/F and t1/2 of disopyramide / varied from 5263 mL/h and 9.95 hours in mild renal / function impairment to 3428 mL/h and 14.47 h in severe renal function impairment, respectively, and in / healthy 12 Japanese subjects mean CL/F and t1/2 / were reported to be 6173 mL/h and 6.05 h, respectively 12) . These results were in line with the study reported by Francois et al 2) . Since disopyramide Cmax was not affected, renal function impairment would affect disopyramide elimination from the body but not its absorption.…”
Section: Discussionsupporting
confidence: 94%
“…As reported in previous studies in Caucasian population 2,3) , renal function impairment affected the pharmacokinetics of disopyramide and its metabolite, monoisopropyl disopyramide. In our / present study, mean CL/F and t1/2 of disopyramide / varied from 5263 mL/h and 9.95 hours in mild renal / function impairment to 3428 mL/h and 14.47 h in severe renal function impairment, respectively, and in / healthy 12 Japanese subjects mean CL/F and t1/2 / were reported to be 6173 mL/h and 6.05 h, respectively 12) .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, MND concentration would be expected to be only about 0.5 mgfL in this setting (Aitio et al 1981), and a contribution of MND to disopyramide's pharmacological effects therefore cannot be excluded by this study. Single-dose studies of disopyramide pharmacokinetics in patients with renal failure have shown that although maximum concentration achieved after an oral dose is little changed, there is substantial difference in other parameters (Burk & Peters 1983;Francois et al 1983). Time to maximum concentration following an oral dose (tmaJ is increased by approximately 50% in the presence of renal failure, and volume of distribution (V d) is reduced by one-third.…”
Section: Metabolite Pharmacological Activitymentioning
confidence: 98%